Public reality construction: Framing theory by detik.com in packaging PSI political information (BIS Humanities and Social Science, 2025)
In the context of this study, researchers took the case of framing analysis conducted by detik.com media on the political news of the Partai Solidaritas Indonesia. The purpose of this research is to analyze how online media, especially detik.com, frames political news related to the Partai Solidaritas Indonesia (PSI) using the framing theory proposed by Robert N. Entman. This research seeks to investigate how detik.com presents information from PSI that is not just informative, but also strategic in influencing public perception. The research will look at whether detik.com is more likely to highlight successes or failures in its coverage of PSI. The method used is a qualitative research method with a case study approach. This research uses content analysis by collecting primary data from detik.com news narratives related to PSI. The focus of this research is on framing in news presentation, which aims to provide insight into media communication strategies in a complex political landscape. The framing done by detik.com highlights certain aspects of PSI's political news, such as official statements from party leaders and reactions to current political issues, which can strengthen or weaken PSI's image in the eyes of the public. The results of this study show that detik.com framed PSI by focusing on the figure of Kaesang, which is reflected in the selection of headlines and news context used. This success can be seen from the increase in PSI's electability in the last general election.